A novel non-invasive treatment in deep burned patients who do not have consent to surgery - Seyed Hassan Tavoosi; Ali Ahmadabadi; Omid Yazarlou; Hossain Safari; Mahdi Kouhi Noghondar; Elaheh Emadi; Daryoush Hamidi Alamdari (Burns Open)
One of the common traumatic injuries is burns. In deep burns, the standard of care (SOC) is surgical excision and skin grafting, still, some patients do not have consent to do the surgical procedure because of operation fear, comorbidity disorder, or contraindications for anesthesia. This study applied a novel repairing gel, also called SUPRAZ, to treat patients with deep burns to achieve outcomes similar to those of SOC. This gel was made from approved biochemical components involved in wound healing mechanisms. Over 18 months, from 2022 to 2024, this controlled single-arm clinical trial including 22 patients aged 4–80 years with deep partial or/and full thickness burns covering 0.5–12 % of their total body surface area was conducted. Despite the emphasis on surgery, these patients did not consent to do surgery. Therefore, repairing gel was applied topically on the burn area. Repairing gel time to heal the area of burns was 24.9 ± 8.5 (mean ± SD; days). The pain subsided after 10–15 min of use. During the 3–12 months follow-up of the patients, there were no signs of hypertrophic scars and keloids. The repairing gel was safe and can be used for patients who do not consent to surgery. Multicenter clinical trials are needed to substantiate the efficacy of repairing gel and achieving comparable long-term results to SOC in deep-burned patients. Trial registration: IRCT20191228045924N6.